2020
DOI: 10.3390/healthcare8040440
|View full text |Cite
|
Sign up to set email alerts
|

Online University Counselling Services and Psychological Problems among Italian Students in Lockdown Due to Covid-19

Abstract: Introduction: With the advent of Covid-19, Italian university students were overwhelmed by fear of the pandemic and the social restrictions of the lockdown phase, with all didactic activity provided online. These stress factors caused people to experience psychological problems and/or the aggravation of pre-existing mental symptomatology. Psychological support is, therefore, important for the university-student population. Aims: (1) Analyzing the psychological difficulties and mental problems relative to lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 46 publications
(63 reference statements)
4
32
0
3
Order By: Relevance
“…Previous studies underlined the effectiveness of online support interventions, which have been carried out both to help students with problems inherent to their academic path (motivation and reorganization of the study) and to take care of their psychological, emotional, and relational needs related to the COVID-19 pandemic [ 15 , 25 , 26 ]. Specific interventions should thus be employed to manage the negative effects of the COVID-19 outbreak on the psychological well-being of university students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies underlined the effectiveness of online support interventions, which have been carried out both to help students with problems inherent to their academic path (motivation and reorganization of the study) and to take care of their psychological, emotional, and relational needs related to the COVID-19 pandemic [ 15 , 25 , 26 ]. Specific interventions should thus be employed to manage the negative effects of the COVID-19 outbreak on the psychological well-being of university students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzing the mental health of university students found lower levels of anxiety and stress symptoms, evaluated through the GAD-7 and the PSS-10 questionnaires, compared to those of our sample of university students [42][43][44]. This is not surprising, since the COVID-19 pandemic had a worsening effect on the general population and on university students in particular: a research study conducted on Italian university students to identify psychological consequences of the living conditions during the COVID-19 lockdown reported high levels of anxiety and stress, concentration disorders, psychosomatization, and, in several cases, reactivation of trauma and worsened sleep quality [46]. Moreover, from the time of our baseline assessment until the end of our study, the COVID-19 pandemic in Italy reached higher levels of infection, which required more severe restrictions to be introduced in schools and universities (ie, full online teaching) and in citizens' everyday lives.…”
Section: Principal Findingsmentioning
confidence: 73%
“…Student support was completely redefined during the acute transition to coping with isolation and learning simultaneously. High levels of anxiety and stress and the resurgence of pre-existing mental disorders identified through structured interviews were expected [ 31 ]. Addressing them through counseling and psychoeducational interventions was necessary.…”
Section: Discussionmentioning
confidence: 99%